Effectiveness of Communication Strategy in Disaster Management in Indonesia - Soelistyowati, Rr Dinar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research explores the effectiveness of communication strategies in disaster management in Indonesia, focusing on the utilization of modern technology, social media, and community engagement. The study used a qualitative-descriptive approach, analyzing case studies of the Lombok earthquake and Palu tsunami to evaluate the successes and challenges of disaster communication. The research findings show that social media and community training play an important role in improving community preparedness and response to disasters. However, challenges such as limited communication infrastructure in remote areas still hamper the effectiveness of these strategies. Recommendations include developing communication technology, establishing a dedicated communication team, and improving education and coordination between stakeholders to optimize disaster communication in the future